A study of the clover root nodule bacteria (Rhizobium trifolii dangeard) in soils of the George district - Loos, Michael (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1963.